REL-1017 (Esmethadone) Increases Circulating BDNF Levels in Healthy Subjects of a Phase 1 Clinical Study - De Martin, Sara; Gabbia, Daniela; Folli, Franco; Bifari, Francesco; Fiorina, Paolo; Ferri, Nicola; Stahl, Stephen; Inturrisi, Charles E.; Pappagallo, Marco; Traversa, Sergio; Manfredi, Paolo L. (Frontiers in Pharmacology, 2021)
Brain-derived neurotrophic factor (BDNF), a neurotrophin widely expressed in the central nervous system, exhibits important effects on neural plasticity. BDNF has been implicated in the mechanism of action of ketamine, a N-methyl-D-aspartic acid receptor (NMDAR) antagonist with rapid anti-depressant effects in humans. REL-1017 (esmethadone), the d-optical isomer of the racemic mixture d-l-methadone, is devoid of clinically relevant opioid activity at doses expected to exert therapeutic NMDAR antagonistic activity in humans. The present study was conducted to ascertain the effects of oral administration of 25 mg of REL-1017 for 10 days on plasma BDNF in healthy subjects confined to an inpatient unit for a Phase 1 clinical trial. We observed an increase in post-treatment BDNF plasma levels compared to pre-treatment levels. Post-treatment, Day 10 BDNF plasma levels ranged from 2 to 17 times pre-treatment levels in the 25 mg REL-1017 treatment group, whereas in the placebo group, BDNF plasma levels remained unchanged (p=0.028). Diastolic blood pressure decreased significantly in subjects treated with REL-1017, while no effect could be observed in the placebo group. In conclusion, the administration of 25 mg REL-1017 significantly increased BDNF plasma levels and significantly decreased diastolic blood pressure in healthy subjects confined to an inpatient unit for a Phase 1 clinical trial.